Classroom Size and the Prevalence of Bullying and Victimization: Testing Three Explanations for the Negative Association - Garandeau, Claire F.; Yanagida, Takuya; Vermande, Marjolijn M.; Strohmeier, Dagmar; Salmivalli, Christina (Frontiers in Psychology, 2019)
Classroom size - i.e., the number of students in the class - is a feature of the classroom environment often found to be negatively related to bullying or victimization. This study examines three possible explanations for this negative association: a) it is due to measurement effects and therefore only found for peer-reports (Hypothesis 1), b) bullying perpetrators are more popular and have more friends in smaller classrooms (Hypothesis 2), c) targets of bullying are more popular and have more friends in larger classrooms. Multilevel regression analyses were conducted on a sample from Austria (1,451 students; Mage = 12.31; 77 classes) and a sample from the Netherlands (1,460 students; Mage = 11.06; 59 classes). Results showed that classroom size was negatively associated with peer-reported bullying and victimization in both samples, and with self-reported bullying and victimization in the Dutch sample only, suggesting partial support for Hypothesis 1. Students high in bullying were found to be more popular in smaller than in larger classrooms in the Austrian sample. The negative link between victimization and popularity was found to be stronger in smaller classrooms than in larger classrooms in the Dutch sample. However, classroom size was not found to moderate links between bullying or victimization and friendship in either sample. Hypotheses 2 and 3 were supported, but only for popularity and in a single sample. Further research is needed to better understand the higher prevalence of bullying found in smaller classrooms in many studies.